Neurotransmitter receptor densities are associated with changes in regional Cerebral blood flow during clinical ongoing pain. Issue 17 (7th July 2022) - Vamvakas, Alexandros; Lawn, Timothy; Veronese, Mattia; Williams, Steven C. R.; Tsougos, Ioannis; Howard, Matthew A.
Abstract: Arterial spin labelling (ASL) plays an increasingly important role in neuroimaging pain research but does not provide molecular insights regarding how regional cerebral blood flow (rCBF) relates to underlying neurotransmission. Here, we integrate ASL with positron emission tomography (PET) and brain transcriptome data to investigate the molecular substrates of rCBF underlying clinically relevant pain states. Two data sets, representing acute and chronic ongoing pain respectively, were utilised to quantify changes in rCBF; one examining pre‐surgical versus post‐surgical pain, and the second comparing patients with painful hand Osteoarthritis to a group of matched controls. We implemented a whole‐brain spatial correlation analysis to explore associations between change in rCBF (ΔCBF) and neurotransmitter receptor distributions derived from normative PET templates. Additionally, we utilised transcriptomic data from the Allen Brain Atlas to inform distributions of receptor expression. Both datasets presented significant correlations of ΔCBF with the μ‐opioid and dopamine‐D2 receptor expressions, which play fundamental roles in brain activity associated with pain experiences. ΔCBF also correlated with the gene expression distributions of several receptors involved in pain processing. Overall, this is the first study illustrating the molecular basis of ongoing pain ASL indices and emphasises the potential of rCBF as a biomarker in pain research. Abstract : Arterial spin labelling (ASL) plays an increasingly important role in neuroimaging pain research but does not provide molecular insights regarding how rCBF relates to underlying neurotransmission. Here, we integrate ASL with PET and brain transcriptome data to investigate the molecular substrates of rCBF, underlying clinically relevant pain states. Both datasets presented significant correlations of ΔCBF with the μ‐opioid and dopamine‐D2 receptor expressions, which play fundamental roles in brain activity associated with pain experiences, as well as with the gene expression distributions of several receptors involved in pain processing.